2012
DOI: 10.1618/jhes.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Improvements of the Traditional Houses in Nepal for the Sustainable Building Design

Abstract: The traditional architecture could be one of the key issues for sustainable building design for different climates and cultures. They are well matched and adapted to the climates and cultures by using local building materials and techniques. However, traditional forms of architecture are decreasing dramatically, being replaced by artificial materials, modern designs and alien technology. We need strong policies and sound research to sustain the concepts and practicalities of traditional architecture. Thus, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Some [21] studied the physiological adaptation of the original inhabitants of an area. Some others [22][23][24][25][26][27][28] focused on the building technologies or designs that improve thermal comfort whilst others dealt with the effect of the special thermal environment on occupants' thermal comfort in these areas. The majority of Tibet lies within the 'cold' and the 'severe cold' zones of China [29], which, according to several studies in these climate zones, have a lower comfort temperature range than those in warmer zones, [10,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Some [21] studied the physiological adaptation of the original inhabitants of an area. Some others [22][23][24][25][26][27][28] focused on the building technologies or designs that improve thermal comfort whilst others dealt with the effect of the special thermal environment on occupants' thermal comfort in these areas. The majority of Tibet lies within the 'cold' and the 'severe cold' zones of China [29], which, according to several studies in these climate zones, have a lower comfort temperature range than those in warmer zones, [10,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Energy use (heating and cooling appliances) is positively related to households' thermal environment and people's thermal comfort-the households of inner-city in Kathmandu holding compact settlements of traditional and modern buildings. As evidence, Rijal et al [33] and Rijal [34] investigated that traditional houses had high-temperature control in summer and winter due to local traditional material, opening size, clothing adjustment, and food culture. Besides, Gautam et al [35] investigated thermal acceptability between local and migrant peoples and identified that local people appear more tolerant and saving behavior than migrants due to physio-psychological expectation.…”
Section: Discussion and Policy Considerations For Gender Participationmentioning
confidence: 99%
“…Indoor thermal environment investigation is an emerging research area that is closely related to building energy consumption and plays a significant role in creating a comfortable, healthy, and efficient built environment [18]. Over the past decade, a growing trend of studies [19,20] has focused on the thermal environment of housing in temperate regions. For example, Lin et al [18] conducted research on China's cold winter climate and found that the average internal temperature in the bedroom was 12.7 • C, with the lowest acceptable internal temperature without heating at 10 • C. Similarly, Singh et al [21] demonstrated that vernacular buildings in India were significantly uncomfortable in the winter months.…”
Section: Thermal Environmentmentioning
confidence: 99%